Implementasi Teknik Enkripsi Menggunakan Algoritma XXTEA (Corrected Block Tiny Encryption Algorithm) Untuk Penyandian Record Data Pada Database - Rahmadani, Cici (Bulletin of Data Science, 2024)
In this computer era, many schools still implement conventional exam systems or exams using leaflets for their students, not a few of the teachers still make their answer keys using paper or put them in files, of course this will be very vulnerable to leaks and anyone will easily find out. Seeing the vulnerability of the answer key, the school or teachers must act so that there are no unwanted incidents, therefore the answer key sheets that are easy to find out must be immediately secured from irresponsible people by using cryptography techniques. Security techniques using cryptography are very appropriate for this, because cryptography is the science or art of security in cryptography there are many algorithms that can change clear text into ciphertext or encrypted messages that are only known by certain people so that the answer key cannot be easily read by irresponsible people.